3296 Endometrial cancer microbiome biomarker for disease detection and microbial role in the disease. (27th March 2019) - Walther-Antonio, Marina; Walsh, Dana; Liu, Yuguang; Yao, Janet; Chia, Nicholas; Nelson, Heidi; Mariani, Andrea
Abstract : OBJECTIVES/SPECIFIC AIMS: Our primary objective is to determine whether the bacteria exerts its effect intra- or extra-cellularly. We have genomic and microscopy preliminary evidence indicating that the bacteria is capable of invading endometrial cells. Our secondary objective is to identify what type of impact the bacteria have on the host cells and whether they are capable of transforming the host cells from a benign into a malignant phenotype. We are currently testing a putative mechanism by which the bacteria may cause the overexpression of the hypoxia inducible factor (HIF), a hallmark of endometrial cancer. METHODS/STUDY POPULATION: We are utilizing our custom built optofluidics platform (microfluidics platform incorporated into an advanced microscope with optical laser tweezers) to isolate single cells from the endometrial tissues of 150 patients with and without endometrial cancer. We are utilizing single cell whole genome amplification followed by qPCR to identify if the bacteria is present intracellularly. We are coupling this procedure with standard microbiological invasion assays with endometrial cell line cultures and P.somerae. We are also utilizing our optofluidics platform to perform single cell transcriptomic amplification, followed by sequencing of cells invaded or in the presence of the bacteria to determine the impact in the transcriptome of the host cell. We are coupling this with western blots of factors hypothesized to be impacted by the bacteria in the overexpression of HIF. RESULTS/ANTICIPATED RESULTS: Based on our preliminary data we anticipate to find evidence that P.somerae is invading the host cells, in particular the cells in tumor tissues. We also expect to find that the intracellular presence of the bacteria is causing the overexpression of the HIF pathway, hence resulting in a cancerous phenotype. DISCUSSION/SIGNIFICANCE OF IMPACT: Our long-term goal is to develop primary prevention strategies that will reduce endometrial cancer incidence rates. A confirmation of our hypothesis could suggest that it is sufficient for endometrial cancer prevention efforts to eliminate P.somerae, in line with gastric and cervical cancer efforts. It could also mean that targeting P.somerae in cancer treatment is necessary to contain the disease and prevent recurrence.